Analisis Tingkat Self-Confidence Siswa dalam Pembelajaran Matematika di SMA Negeri 8 Tanjung Jabung Barat - Yola Wulandari; Anika Pratiwi; Naila Nur Fathimah; Silvia Putri Anggraini; Novferma; Wardi Syafmen (STKIP Subang, 2026)
This study aims to analyze the level of students’ self-confidence in mathematics learning at SMA Negeri 8 Tanjung Jabung Barat. This research employed a descriptive quantitative approach using a survey method. The participants consisted of 61 Grade X students selected through purposive sampling. Data were collected using a closed-ended questionnaire with a Likert scale consisting of 24 statements developed based on Lauster’s self-confidence theory and adapted into four dimensions: Self-Belief, Optimism, Assertiveness, and Independence. Data analysis was conducted descriptively by calculating percentage scores and classifying them into five categories: Very High, High, Medium, Low, and Very Low. The findings showed that most students were in the High category (57.4%), followed by Medium (27.9%), Very High (13.1%), and Low (1.6%), while no students were categorized as Very Low. Analysis of each dimension indicated that Optimism was the strongest dimension (81.2%), whereas Independence was the weakest (70.5%). These findings indicate that students generally demonstrate good self-confidence in mathematics learning; however, learning strategies that further encourage independent learning still need to be strengthened.